Obtaining and investigation of epoxide rapeseed oil as a modifier for road bitumen - Гринчук, Юрій Миколайович; Старчевський, Володимир Людвікович; Никипанчук, Михайло Васильович; Гринчук, Володимир Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
Petroleum bitumen, used for making asphalt coatings do not always meet the high quality standards. Therefore, they are modified by various modifiers. It was found that bitumen epoxy compounds of higher olefins based on renewable raw materials allows improving the operational characteristics of road surfaces. An urgent need of this work is to obtain epoxide rapeseed oil and to determine its properties in particular thermal stability. The most widespread way of preparation of epoxy rapeseed oils is epoxidation in the medium of formic acid and hydrogen peroxide. A thermal stability was investigated by comprehensive thermogravimetric, differential and thermal analysis, and infrared spectroscopy. Analyzing the results of comprehensive thermogravimetric, differential and thermal analysis and infrared spectroscopy, we can conclude that the ERO heating of to 130 ° C, it is thermally stable. These data allow us to determine the optimal conditions for making compositions for bitumen modification. Also in the the course of work we proposed a way epoxidation of oils by cutting process stages and without the use of solvent